2009
DOI: 10.1002/jor.20836
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mechanical properties for optimal fluid motion inside artificial bone substitutes

Abstract: Our goal was to develop a method to identify the optimal elastic modulus, Poisson's ratio, porosity, and permeability values for a mechanically stressed bone substitute. We hypothesized that a porous bone substitute that favors the transport of nutriments, wastes, biochemical signals, and cells, while keeping the fluid-induced shear stress within a range that stimulates osteoblasts, would likely promote osteointegration. Two optimization criteria were used: (i) the fluid volume exchange between the artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…One of the major results showed that due to the different loading situations found in the body, scaffolds should be tailored specifically for each implantation site. This loading-specific approach in the development of scaffolds has been recently taken into account in the development of an algorithm optimising the fluid flow to maximise transport, while keeping the shear stress on cells within an osteogenic range (Blecha et al 2009). …”
Section: Computer Methods For Bone Tissue Engineering Mechanotransducmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major results showed that due to the different loading situations found in the body, scaffolds should be tailored specifically for each implantation site. This loading-specific approach in the development of scaffolds has been recently taken into account in the development of an algorithm optimising the fluid flow to maximise transport, while keeping the shear stress on cells within an osteogenic range (Blecha et al 2009). …”
Section: Computer Methods For Bone Tissue Engineering Mechanotransducmentioning
confidence: 99%
“…Based on this need, an analytical model has been developed allowing to optimise the fluid flow exchange between the scaffold and its surrounding, while maintaining the value of shear stress on cells within physiological ranges (Blecha et al 2009). The advantages of the analytical approach reside in an effective parameter study, particularly determining the impact of the elastic modulus, Poisson's ratio, porosity and permeability of the scaffold on fluid motion, which is complementary to numerical studies (e.g.…”
Section: Translation Of Mechanotransduction Knowledge In the Developmmentioning
confidence: 99%
“…For bone tissue engineering, one of the main challenges in creating such a scaffold is that the mechanical characteristics of the scaffold will change as it degrades and allows the perfusion of nutrients and solutes [30,31,33,34]. Therefore the foundation of this design rests on the need for increased bone formation during repair to compensate and increase the mechanical strength of the defect as the mechanical properties of the scaffold decrease [30,33,34].…”
Section: Tissue Engineering For Bone Regenerationmentioning
confidence: 98%
“…This combination has been formally described in the development of an artificial bone scaffold by optimising properties such as elastic modulus, permeability, Poisson coefficient and porosity to maximise the fluid exchange in the scaffold while keeping the flow induced-shear stress at an osteoinductor level (Blecha et al 2009). The knowledge of the value of the mechanical stimulus is then central to obtain an increase in bone formation in the scaffold.…”
Section: New Paradigm In Bone Tissue Engineeringmentioning
confidence: 99%